Performance of three iGrav superconducting gravity meters before and after transport to remote monitoring sites. Issue 2 (28th July 2020) - Schäfer, Florian; Jousset, Philippe; Güntner, Andreas; Erbas, Kemal; Hinderer, Jacques; Rosat, Séverine; Voigt, Christian; Schöne, Tilo; Warburton, Richard
SUMMARY: High spatial and temporal resolution of gravity observations allows quantifying and understanding mass changes in volcanoes, geothermal or other complex geosystems. For this purpose, accurate gravity meters are required. However, transport of the gravity meters to remote study areas may affect the instrument's performance. In this work, we analyse the continuous measurements of three iGrav superconducting gravity meters (iGrav006, iGrav015 and iGrav032), before and after transport between different monitoring sites. For 4 months, we performed comparison measurements in a gravimetric observatory (J9, Strasbourg) where the three iGravs were subjected to the same environmental conditions. Subsequently, we transported them to Þeistareykir, a remote geothermal field in North Iceland. We examine the stability of three instrumental parameters: the calibration factors, noise levels and drift behaviour. For determining the calibration factor of each instrument, we used three methods: First, we performed relative calibration using side-by-side measurements with an observatory gravity meter (iOSG023) at J9. Secondly, we performed absolute calibration by comparing iGrav data and absolute gravity measurements (FG5#206) at J9 and Þeistareykir. Thirdly, we also developed an alternative method, based on intercomparison between pairs of iGravs to check the stability of relative calibration before and after transport to Iceland. The results show that observed changes of the relative calibration factors by transport were less than or equal to 0.01 per cent. Instrumental noise levels were similar before and after transport, whereas periods of high environmental noise at the Icelandic site limited the stability of the absolute calibration measurements, with uncertainties above 0.64 per cent (6 nm s –2 V –1 ). The initial transient drift of the iGravs was monotonically decreasing and seemed to be unaffected by transport when the 4K operating temperatures were maintained. However, it turned out that this cold transport (at 4 K) or sensor preparation procedures before transport may cause a change in the long-term quasi-linear drift rates (e.g. iGrav015 and iGrav032) and they had to be determined again after transport by absolute gravity measurements.